Four new species of Mesoamerican biting midges of the genus Culicoides (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2015)
Fil: Spinelli, Gustavo Ricardo. División Entomología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina